Low cost micropropagation of pineapple: a review / Nurul Najwa Che Abdul Mubin - Che Abdul Mubin, Nurul Najwa (Faculty of Plantation and Agrotechnology, 2018)
Pineapple (Ananascomosus L.) is a vegetative propagated crop and it belongs to the family Bromeliaceae and have adapted to a very wide range of habitats. Vegetative organs such as sucker, slip and crown are used as a conventional propagation of pineapple but it has been reported to produce low multiplication rate. Through biotechnological approach, micropropagation technology could help in increasing the rates of multiplication. However,micropropagated shoots are relatively expensive due to the components used in micropropagation technique. According to previous research, it could be stated that the result of using alternative components in micropropagation technique could reduce the overall cost such as commercial sugar was used to replace sucrose and the liquid media that commercially cheaper that solid media also used to eliminate the cost of agar. Then, tap water also has been to replace double distilled water. Other than that, pressure cooker was used as an equipment to replace an autoclave that is more expensive to sterilize the media. This alternative could reduce the cost of micropropagation. Hence, by using other alternative in micropropagation technique, it can help in reducing the overall cost for micropropagation process.